Elusive promises : planning in the contemporary world - Abram, Simone (Dislocations, 2013)
Planning in contemporary democratic states is often understood as a range of activities, from housing to urban design, regional development to economic planning. This volume sees planning differently-as the negotiation of possibilities that time offers space. It explores what kind of promise planning offers, how such a promise is made, and what happens to it through time. The authors, all leading anthropologists, examine the time and space, creativity and agency, authority and responsibility, and conflicting desires that plans attempt to control. They show how the many people involved with.